Some problems of legal regulation of intellectual property objects on the Internet - Nikishkin A. V., Nikishkina A. A., Sachenko A. L. (Relevant issues of management, economics and economic security, 2024)
The article deals with topical issues related to the legal regulation of intellectual property on the Internet, due to the development of digital technologies. The main problems relate to the legality of the use of user-generated content and liability for intellectual property violations. The authors emphasize the complexity of law enforcement in a global network environment where the boundaries of jurisdiction are blurred and the necessary legislative definitions are missing.
Keywords: интеллектуальная собственность; интернет; Internet; цифровые технологии; правовое регулирование; digital technologies; legal regulation; intellectual property; объекты интеллектуальных прав; objects of intellectual rights